DETERMINATION OF TAX AVOIDANCE PRACTICES - Angelie Viantiaraini; Haninun Haninun; Riswan Riswan (Transpublika Publisher, 2024)
To enhance tax revenue, the government is continuously working towards strengthening the tax sector's contribution to funding state expenses. However, a major hurdle in achieving the desired tax earnings is the prevalence of tax avoidance practices. This research aims to delve into the influence of company size, leverage, and sales growth on tax avoidance in f&b firms listed on the Indonesia Stock Exchange from 2018 to 2022. The study examines company size, leverage, and sales growth as independent variables, while tax avoidance serves as the dependent variable. The analysis encompasses 84 f&b firms listed on the Indonesia Stock Exchange during the specified period, with a sample size of 26 companies selected through purposive sampling. The data was analyzed using multiple regression tests with the aid of SPSS 18 software. The findings of this study reveal that company size does not significantly impact tax avoidance. However, leverage exhibits a positive effect on tax avoidance, whereas sales growth demonstrates a negative effect on tax avoidance.